2009
DOI: 10.1007/s11270-009-0071-3
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Factors of Ta, Th, and U Oxides Present in Pyrochlore

Abstract: Air pollution can be a problem in industrial processes, but monitoring and controling the aerosols in the work place is not enough to estimate the occupational risk due to dust particle inhalation. The solubility in lung fluid is considered to estimate this risk. The aim of this study is to determine in vitro specific dissolution parameters for thorium (Th), uranium (U), and tantalum (Ta) associated to crystal lattice of a niobium mineral (pyrochlore). Th, U, and Ta dissolution factors in vitro were obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Using ion chromatography, they found that 99% of S in particles smaller than 2 mm was soluble ammonium sulfate. Brazilan researchers, 42 in a study evaluating the occupational risk due to dust particle inhalation, determined the solubility of Ta, Th and U oxide species contained in pyrochlore (a niobium mineral) dust particles when subjected to a simulant lung fluid (Gamble solution). These experimentally derived dissolution factors were in broad agreement with calculated dissolution factors from worker exposure studies involving air monitoring and subsequent biomonitoring using faecal and urine samples.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Using ion chromatography, they found that 99% of S in particles smaller than 2 mm was soluble ammonium sulfate. Brazilan researchers, 42 in a study evaluating the occupational risk due to dust particle inhalation, determined the solubility of Ta, Th and U oxide species contained in pyrochlore (a niobium mineral) dust particles when subjected to a simulant lung fluid (Gamble solution). These experimentally derived dissolution factors were in broad agreement with calculated dissolution factors from worker exposure studies involving air monitoring and subsequent biomonitoring using faecal and urine samples.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In anthropized areas people are exposed to the almost constant inhalation of lithogenic and anthropogenic atmospheric dust delivered from natural sources, automotive traffic, and/or industrial activities. Effects on human health related to the inhalation of these atmospheric particulates are mainly recognized as precursors of silicosis, asbestosis, and cancers, whereas only a scarce literature is available focused on effects of the dissolution of atmospheric dust in the presence of human bronchial fluids. This represents a lack of knowledge since environmental solids are often a source of concentrated metallic elements that can be released in biological fluids, and the amplitude of trace elements leachable from these solids depends from their composition and nature. , …”
Section: Introductionmentioning
confidence: 99%